μ-Bromido-bis{μ-2,2′-[4,7-diazadecane-1,10-diylbis(nitrilomethanylylidene)]diphenolato}tricopper(II) bromide dimethylformamide disolvate - Assey, Gervas (International Union of Crystallography, 2011)
The complex molecule of the title compound, [Cu(3)Br(C(22)H(28)N(4)O(2))(2)]Br·2C(3)H(7)NO, contains three copper atoms, two of which are five-coordinate within a square-pyramidal environment and linked by a bridging Br atom occupying the apical position in each square pyramid. The remaining Cu atom is four-coordinate but with considerable tetrahedral disortion [the dihedral angle between the two chelate planes is 69.21 (7)°]. There are two molecules of dimethylformamide (DMF) present as solvent molecules, one of which is disordered over two equivalent conformations with occupancies of 0.603 (5) and 0.397 (5). The amine H atoms are involved in both inter- and intramolecular hydrogen-bonding interactions with the Br and O atoms of the cation, as well as with the O atom of the ordered DMF molecule.